Implementasi Asas Ultimum Remidium Terhadap Anak Sebagai Penyalahguna Narkotika (Studi Putusan Nomor 37/Pid.Sus-Anak/2022/PN Mdn) - Waruwu, Noman Tuboiman; Frensh, Wenggedes; Muazzul, Muazzul (JUNCTO: Jurnal Ilmiah Hukum, 2023)
Criminal sanctions should be an (ultimum remedium) last remedy if other criminal means are unable to overcome. Children who are caught in legal cases as drug abusers are not fully perpetrators and criminals who must be punished like adults. This study aims to determine the application of the ultimum remedium principle to children as drug abusers. The research method used is normative legal research method or also called library legal research or research that looks at library materials (secondary data). Normative legal research as a way to build a system of norms about principles, norms, legal rules, agreements, and doctrines, as well as court decisions. The results showed that the application of the ultimum remedium principle against children is the last resort and the imposition of punishment must be non-custodial.